2000
DOI: 10.1200/jco.2000.18.1.148
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Active Specific Immunotherapy for Stage II and III Colon Cancer With an Autologous Tumor Cell Vaccine: Eastern Cooperative Oncology Group Study E5283

Abstract: When all randomized patients were evaluated, no significant clinical benefit was seen with ASI in surgically resected colon cancer patients with stage II or III colon cancer. However, there was an indication that treatment compliance with effective immunization results in disease-free and overall survival benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
94
0
5

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(100 citation statements)
references
References 18 publications
1
94
0
5
Order By: Relevance
“…This is important because DTH-reactions indicate the development of specific cellular immunity and correlate strongly with survival (McCune et al, 1990;Baars et al, 2000;Harris et al, 2000). A recently published study with autologous colon tumour vaccines has shown that DTH-reactions with a diameter exceeding 10 mm should be considered to reflect successful vaccination therapy and predict relatively good survival rates (Harris et al, 2000).…”
Section: -Fu+asi For Stage III Colon Cancer a Baars Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…This is important because DTH-reactions indicate the development of specific cellular immunity and correlate strongly with survival (McCune et al, 1990;Baars et al, 2000;Harris et al, 2000). A recently published study with autologous colon tumour vaccines has shown that DTH-reactions with a diameter exceeding 10 mm should be considered to reflect successful vaccination therapy and predict relatively good survival rates (Harris et al, 2000).…”
Section: -Fu+asi For Stage III Colon Cancer a Baars Et Almentioning
confidence: 99%
“…The presence of a DTH response to tumour cells, 48 h after the vaccination regimen, is a measure of immunogenicity and reflects the adequacy of the vaccination and the general immune status of the patient. So far, DTH has been the only suitable parameter for the evaluation of anti-tumour immunity and the best early predictor of clinical efficacy of vaccination therapies (McCune et al, 1990;Harris et al, 2000;Baars et al, 2000;Clay et al, 2001).…”
mentioning
confidence: 99%
“…Assays such as the enzyme-linked immunospot (ELISpot), an interferon-γ-release assay which can detect the frequency of specific cytotoxic lymphocytes, are gaining popularity, but the relative importance of any positive result to clinical outcome remains unclear. The assay which currently appears in a number of trials to correlate most strongly with a clinical response is delayed-type hypersensitivity (DTH) testing (Berd et al, 1990;Simons et al, 1997;Harris et al, 2000).…”
Section: Evaluation Of Vaccine Therapy: the Importance Of Immunologicmentioning
confidence: 99%
“…Whole tumor cell vaccines combined with bacilli Calmette-Guerin (BCG), an attenuated strain of mycobacterium bovis, was the first colorectal tumor cell vaccine. Then three randomized trials of this tumor cell BCG vaccine have been carried out (Hoover et al, 1993;Vermorken et al, 1999;Harris et al, 2000). Regrettably, a meta-analysis of these three trials showed that overall survival trended towards improvement but failed to reach statistical significance.…”
Section: Introductionmentioning
confidence: 99%